Penyisihan COD, TSS, dan TN pada Lindi TPA Klotok Menggunakan Anoxic-Oxic Moving Bed Biofilm Reactor - Tasya Ambar Aimia; Naniek Ratni JAR (Yayasan Literasi Sains Indonesia, 2023)
Leachate is a liquid containing extracted, dissolved, and suspended materials from waste in a landfill. Leachate from Klotok landfill contains pollutant loads that do not meet the water quality standards, necessitating treatment. In this study, parameters considered were COD, TSS, and TN. Anoxic-Oxic Moving Bed Biofilm Reactor (MBBR) was chosen due to its compact footprint, low sludge production, ability to handle high COD loads, and not requiring periodic backwash. Variations including media type, media volume, and Hydraulic Retention Time (HRT) were applied to reduce pollutant parameter concentrations. The experiment was conducted in batch-continuous mode. The derived parameter concentrations yielded promising results using a biocube/sponge media in the reactor, constituting 50% of the leachate volume, with an HRT of 45 hours. Upon continuous operation under the best variations for parameter reduction, COD, TSS, and TN values were achieved as 160 mg⁄L, 132 mg⁄L, and 31.5 mg⁄L, respectively. Meanwhile, the average removal percentages for COD, TSS, and TN were 87%, 50%, and 87% respectively. Additionally, microorganism identification was performed in the anoxic-oxic moving bed biofilm reactor, revealing the presence of microorganisms such as coliforms, Bacillus sp., and Pseudomonas sp.